Investigation of Live-Bed Scour at Labyrinth Side Weirs - Tunç, Mustafa; Emiroğlu, M. Emin (Fırat University, 2018)
Side weirs, also known as lateral weirs, and overflow dams are free overflow regulation and diversion devices commonly encountered in hydraulic engineering. The lateral loss of water is reducing the sediment transport capacity in the main-channel and the formation of a local sediment deposit in the downstream of weir. The head over the side weir rises and the side overflow discharge as well. The design discharge to be diverted over the weir is increased by this flow-sediment transport interaction. Although there were no studies that scrutinized the scouring depth and geometry that occurs around the labyrinth side weirs in channels with movable bed, there are limited number of studies that examined the scouring geometry around the classical side weir. In the present study, local scour depths formed in the periphery of triangular labyrinth side weir mounted in a live-bed rectangular cross-section straight channel were experimentally investigated under steady state flow and free overflow from the side weir conditions. To provide for live-bed conditions, the sediment was added to bed material in the experiments. A series of experiments were conducted for live-bed scouring conditions (for flow intensity greater than one) to determine the maximum scour depths that occur around the triangular labyrinth side weir with different flow depths, different main channel discharges, different volumetric amounts of sediment feed, different crest heights, different Froude numbers, different flow intensities and using uniform bed material. In the experiments, the dimensions of the scours and sediment deposits that occur upstream and downstream of the weir exhibited a periodic change (increase and decrease). The maximum depth of scour occurred at the downstream end of the triangular labyrinth side weir frequently.
Keywords: Engineering; Mühendislik